Microalgae for biofuels: the Portuguese experience - Gouveia, Luisa (2016)
Autotrophic microalgae are photosynthetic organisms that undergo the conversion of light into chemical energy as a form of a wide range of organic compounds through its photosynthetic machinery. The cultivation of microalgae brings environmental advantages, bearing in mind the capability of nutrient recycling in wastewaters together with the fixation of greenhouse gases such as CO2. These micro-organisms have been widely recognized as having huge potential as feedstock for food, feed, pharmaceutical and cosmetic industries (carotenoids, antioxidants, polyunsaturated fatty acids, single-cell proteins (SCP), hycobiliproteins, polysaccharides, vitamins, phytosterols, minerals). Microalgae have also been proposed as a feedstock for bioplastics, agriculture biofertilizers and recently as an energetic vector towards the production of a wide range of biofuels.